A new species of Eugenia sect. Pilothecium (Myrtaceae) from the Atlantic Forest inselbergs of Southeastern Brazil - Faria, Jair E.q.; Fernandes, Thiago (Phytotaxa, 2020)
Eugenia gracilifolia (Myrtaceae), a new species belonging to Eugenia sect. Pilothecium is here described and illustrated with additional comments on morphology, affinities, and conservation. The new species is currently known only from the top of an Atlantic Forest inselberg in the municipality of Teófilo Otoni, State of Minas Gerais, Brazil. It is mainly recognized by its trunk with smooth or rough bark (a novelty for the section), young twigs, abaxial side of the leaves, rachis and flowers densely pubescent, and inflorescences in simple or compound dichasia. The new species is morphologically similar and probably closely related to the widely distributed E. pyriformis differing by its trunk with smooth or rough bark, proportionally longer petioles, leaves with mucronate apex, more delicate inflorescences, obovate flower buds, a larger number of stamens, and pubescent to densely pubescent style.